Analisis Manajemen Risiko Teknologi Informasi pada PT XYZ (Perusahaan Manufacturing) menggunakan Framework COBIT 2019 dengan Domain EDM03 dan APO12 - NYIMAS HAMIDAH PURNAMA AGUSTRIANI (Universitas Muhammadiyah Bangka Belitung, 2024)
The manufacturing industry faces significant information technology risks, which can be managed using a risk management framework such as COBIT 2019. However, PT XYZ, a company that relies heavily on technology, lacks awareness of potential risks. This research examines the risks faced by PT XYZ, evaluates current risk management methods, and explores the application of the COBIT 2019 Framework in risk management. This report provides recommendations for PT XYZ to improve its risk management to increase efficiency and effectiveness. The findings of this research aim to provide concrete and practical recommendations for PT XYZ to improve their overall risk management and business operations. If it does not have the right level of handling, such information technology certainly has risks that cannot be avoided. To overcome this, the ICT department needs to assess the maturity level or capability level of information system risk management. This assessment uses the COBIT 2019 framework with EDM03 and APO12 domains. The results of this research from the ICT Department of PT. XYZ is creating standard and policy documents as well as implementing the IT Risk optimization process well. The achievement of the company's IT Risk management capability level is at level 3 in the EDM03 domain and level 2 in the APO12 domain. These results cannot be separated from limited research access. The GAP level of this company's capabilities is 1 level each, namely level 4 in the EDM03 domain and level 3 in the APO12 domain.